2015
DOI: 10.1038/srep10375
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of high-throughput platforms for validation of a circulating microRNA signature in diabetic retinopathy

Abstract: MicroRNAs are now increasingly recognized as biomarkers of disease progression. Several quantitative real-time PCR (qPCR) platforms have been developed to determine the relative levels of microRNAs in biological fluids. We systematically compared the detection of cellular and circulating microRNA using a standard 96-well platform, a high-content microfluidics platform and two ultra-high content platforms. We used extensive analytical tools to compute inter- and intra-run variability and concordance measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…The differences between TLDA and RT-qPCR protocols (pooled reverse transcription in TLDA vs. individual RT and qPCR; preamplification used in TLDA measurement vs. without preamplification; differences in the reaction volume 1 μl in TLDA vs. 15 μl in individual RT-qPCR) can influence the efficiency of both the RT and qPCR leading to this discrepancy that was found between the two approaches. Also, high variance of the replicates at TLDA system (median: 8.3%; min-max: 0.3-19.1%) has been also described in literature [25].…”
Section: Discussionmentioning
confidence: 57%
“…The differences between TLDA and RT-qPCR protocols (pooled reverse transcription in TLDA vs. individual RT and qPCR; preamplification used in TLDA measurement vs. without preamplification; differences in the reaction volume 1 μl in TLDA vs. 15 μl in individual RT-qPCR) can influence the efficiency of both the RT and qPCR leading to this discrepancy that was found between the two approaches. Also, high variance of the replicates at TLDA system (median: 8.3%; min-max: 0.3-19.1%) has been also described in literature [25].…”
Section: Discussionmentioning
confidence: 57%
“…For example, we recently published a comparison of five different platforms to detect and quantify a microRNA signature for diabetic retinopathy. The different platforms were associated with different sensitivities, sample volumes required, and cost per sample [85]. Maintenance should be kept up to date as poorly maintained or faulty instruments can generate erroneous results.…”
Section: Analytical Factorsmentioning
confidence: 99%
“…Our team is currently taking a discovery rather than a candidate approach to microRNAs for latestage diabetic retinopathy, and recently published a paper highlighting the impact of the instrumentation used for detection of these molecular biomarkers [85]. This new research area holds considerable clinical potential for diagnosis, prognosis, and identifying of potential drug-targets, and even for microRNAs being therapeutic agents themselves.…”
Section: Epigeneticsmentioning
confidence: 99%
“…The result indicated that the synthetic mimics can be successfully discriminated by their respective primer pairs, either the forward primer hsa-miR18a-5p-F/reverse primer hsa-miR-18a-5p-R set or the forward primer hsa-miR-18b-5p-F/reverse primer hsa-miR-18b-5p-R set ( Figure 3a). Despite the range of the Cq value, (this type of range is often observed in nano-volume qPCR platforms (Farr et al 2015), the experiment served the purpose of illustrating the specificity of the primer pairs. In another illustration, the primers designed by specific-FR-system FRM for hsa-miR-16 family members, hsa-miR-16-5p and hsa-miR-195-5p, can distinguish synthetic hsa-miR-16 family oligonucleotide template mimics (Figure 3b).…”
Section: Discriminative Identification Of Mirna Family Using Miprimermentioning
confidence: 99%